2007
DOI: 10.1103/physrevb.75.205326
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure changes ofSi(001)(2×1)from subsurface Mn observed by STM

Abstract: The deposition of Mn atoms onto the Si͑001͒-͑2 ϫ 1͒ reconstructed surface has been studied using scanning tunneling microscopy ͑STM͒ and first-principles electronic structure calculations. Room-temperature deposition of 0.1 ML ͑monolayer͒ of Mn gives rise to a disordered surface structure. After in situ annealing between 300 and 700°C, most of the Mn is incorporated into three-dimensional manganese silicide islands, and Si dimer rows reappear in the STM images on most of the substrate surface. At the same time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 20 publications
5
23
1
Order By: Relevance
“…For instance, under suitable growth conditions, Mn can form a two-dimensional rowlike structure, which could be useful for achieving δ layer doping of silicon by manganese. 38 In this study, Mn was found to be incorporated into Si as an interstitial dopant in good agreement with recent first-principles calculations. [39][40][41] Meanwhile, molecular-beam epitaxy produces samples with mostly substitutional Mn in the Si matrix.…”
Section: Introductionsupporting
confidence: 70%
“…For instance, under suitable growth conditions, Mn can form a two-dimensional rowlike structure, which could be useful for achieving δ layer doping of silicon by manganese. 38 In this study, Mn was found to be incorporated into Si as an interstitial dopant in good agreement with recent first-principles calculations. [39][40][41] Meanwhile, molecular-beam epitaxy produces samples with mostly substitutional Mn in the Si matrix.…”
Section: Introductionsupporting
confidence: 70%
“…The main problem here is similar to that arising in the case of deposition of Mn layers onto the Si surface, when the formation of a silicide ultrathin interface at the boundary between the Si substrate and the Mn layer destroys the magnetic overlayer homogeneity. [19][20][21][22] Nevertheless, under suitable growth conditions, Mn can form a two-dimensional row-like structure, which could be useful for achieving δ-layer doping of silicon by manganese. 20 In this study, Mn was found to be incorporated into Si as an interstitial dopant in good agreement with recent first-principles calculations.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22] Nevertheless, under suitable growth conditions, Mn can form a two-dimensional row-like structure, which could be useful for achieving δ-layer doping of silicon by manganese. 20 In this study, Mn was found to be incorporated into Si as an interstitial dopant in good agreement with recent first-principles calculations. [23][24][25] The interstitial Mn was also observed in thin films irradiated by ultraviolet light releasing metal species into the semiconductor substrate.…”
Section: Introductionmentioning
confidence: 99%
“…While DFT calculations 30 and scanning tunneling microscopy (STM) experiments 31 show that the subsurface sites are more favorable for Mn on Si(001), STM measurements on Mn deposited at room temperature show that Mn adatoms are energetically inhibited from populating these sites at room temperature and instead form chains on the surface. 32,33 By depositing the capping layer prior to annealing, we enabled interactions between the surface Mn layer and the deposited Si that leads to the formation of a MnSi-B20 phase.…”
Section: Xafs Experiments and Analysismentioning
confidence: 99%